A new ranking approach for E-commerce websites based on fuzzy TOPSIS algorithm - Houcine Belouaar; Okba Kazar; Meftah Zouai; Abdelhak Merizig (Institute of Advanced Engineering and Science, 2022)
With the gigantic growth of the E-commerce market, E-commerce websites are becoming more and more numerous. Customers of E-commerce websites are spoiled for choice and have encountered several problems in choosing not only the right products but also the E-commerce website from which they want to purchase the desired products. E-commerce websites ranking is recognized as a complex multi-criteria decision-making (MCDM) problem. In practice, clients of E-commerce websites generally have difficulty expressing their judgments in precise numbers because the criteria are some- times imprecise and sometimes uncertain and ambiguous. In this context, we propose to use fuzzy logic to allow clients to express their ratings in natural language and propose an approach based fuzzy technique for order preference by similarity to the ideal solution (TOPSIS) for E-commerce websites ranking. A numerical experimentation was conducted for validate the effectiveness of the proposed approach.